Counter-terrorism Units of the Police Force of Slovak Republic - Jacek Dworzecki; Izabela Nowicka (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2019)
This study has been dedicated to counter-terrorism forces which form part of the Police Force. Its officers deal with physical neutralisation of terror threats and they take part in fighting against organised crimes on the Slovak Republic territory. The material also addresses the issue of special use of firearms by operators and police sharpshooters who perform their daily duty in specialized counter-terrorism units. The study has been prepared within the framework of the realization of international scientific and research project implemented under the Horizon 2020-FCT-2015 operational programme, No: 700688, entitled: Understand the Dimensions of Organized Crime and Terrorist. Networks for Developing Effective and Efficient Security Solutions for First-Line-Practitioners and Professionals.